«Athlete fingerprinting» of elite ice hockey players and cross-country skiers: towards personalized sports medicine - Maurer, D. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Elite athletes regularly experience impaired performance due to upper respiratory disease (e.g., infections, asthma). Oftentimes, illness-related training interruptions happen during intense periods, such as before or during competitions, which has a major impact on the athlete`s potential success. Apart from injuries, upper respiratory symptoms are the most common reason for elite athlete`s presentation at their sports physician. So far, the reasons for the high prevalence remain unclear. Here, Olink proteomics can provide a better understanding of the underlying mechanisms and help the identification of potential biomarkers of susceptibility to infections, allergic disease and asthma in elite athletes.